2011
DOI: 10.1249/mss.0b013e318207f87b
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nonfunctional Overreaching/Overtraining in Young English Athletes

Abstract: Approximately one-third of young athletes have experienced NFOR/OT, making this an issue for parents and coaches to recognize. OT is not solely a training load-related problem with both physical and psychosocial factors identified as important contributors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
153
3
31

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(190 citation statements)
references
References 27 publications
3
153
3
31
Order By: Relevance
“…Specifically, 29% of 376 young athletes competing at club to international level from 19 different sports reported experiencing overtraining or nonfunctional overreaching at least once (68). Although Matos et al (68) indicated that overtraining or nonfunctional overreaching were not solely a result of physical training load, it is likely that a long-term development plan that fails to allow sufficient time for recovery, adaptation, and natural growth processes will increase the likelihood of negative health outcomes for youth (23). When considering the overall workload of the child or adolescent, it is imperative that practitioners value the quality of practice and competition, as opposed to the quantity of training or competition time.…”
Section: Problem 4: Training Workloads Of Youthmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, 29% of 376 young athletes competing at club to international level from 19 different sports reported experiencing overtraining or nonfunctional overreaching at least once (68). Although Matos et al (68) indicated that overtraining or nonfunctional overreaching were not solely a result of physical training load, it is likely that a long-term development plan that fails to allow sufficient time for recovery, adaptation, and natural growth processes will increase the likelihood of negative health outcomes for youth (23). When considering the overall workload of the child or adolescent, it is imperative that practitioners value the quality of practice and competition, as opposed to the quantity of training or competition time.…”
Section: Problem 4: Training Workloads Of Youthmentioning
confidence: 99%
“…Combined, these factors can theoretically lead to excessive workload accumulation and youth experiencing nonfunctional overreaching (6), overtraining syndrome (74), or burnout (61). Data on youth from the United Kingdom have shown that a relatively high proportion of young athletes have reported experiencing overtraining or nonfunctional overreaching (68). Specifically, 29% of 376 young athletes competing at club to international level from 19 different sports reported experiencing overtraining or nonfunctional overreaching at least once (68).…”
Section: Problem 4: Training Workloads Of Youthmentioning
confidence: 99%
See 3 more Smart Citations